2019
DOI: 10.1111/ctr.13649
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term impact of dialysis‐requiring AKI during the perioperative period of liver transplantation on postdischarge outcomes

Abstract: Background Patients undergoing liver transplantation (LT) are prone to dialysis‐requiring acute kidney injury (AKI‐D). However, long‐term prognoses among them need further investigation, as overall survival after LT is improving. Methods A nationwide, population‐based cohort study was conducted using the data of Korean National Health Insurance System between 2006 and 2015. The patients who received dialysis during the perioperative period of LT were in the AKI‐D group, and the control group included those who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Several factors identified in this analysis have been previously shown in other literature to be significant for prolonged stay following pediatric liver transplant 16 . Specifically, one study illuminated the fact that hemodialysis prior to liver transplant is associated with worse mortality and increased ICU admission 18 . Furthermore, multiple studies found that ICU admission was associated with longer stays, higher mortality, and increased complications 14,19 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Several factors identified in this analysis have been previously shown in other literature to be significant for prolonged stay following pediatric liver transplant 16 . Specifically, one study illuminated the fact that hemodialysis prior to liver transplant is associated with worse mortality and increased ICU admission 18 . Furthermore, multiple studies found that ICU admission was associated with longer stays, higher mortality, and increased complications 14,19 .…”
Section: Discussionmentioning
confidence: 60%
“…Prolonged hospital stay following pediatric liver transplantation is a highly impactful metric which can be correlated to increased Specifically, one study illuminated the fact that hemodialysis prior to liver transplant is associated with worse mortality and increased ICU admission. 18 Furthermore, multiple studies found that ICU admission was associated with longer stays, higher mortality, and increased complications. 14,19 However, though discrete variables from this analysis have been identified as significant in other studies, there is scarce literature that specifically identifies multiple predictive variables and their effects on hospital stay following liver transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, prior studies have found heightened graft loss in recipients requiring RRT posttransplant characterized by greater mortality in this group. [8][9][10] Renal function at 1 year was significantly worse in the RRT group at all time points. This was anticipated as recipients in the RRT group had significantly worse renal function at baseline.…”
Section: Discussionmentioning
confidence: 88%
“…Both RRT and infection were linked with a heightened mortality risk, which has been observed in prior studies. 2,7,8 Although tacrolimus was delayed in an effort to reduce worsening renal dysfunction and infection risk, mycophenolate dosing and prednisone use were higher in the RRT group. Specifically, higher mycophenolate dosing was used by the end of the study, which may have been in response to greater BPAR observed in the RRT group.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies report time disparities in kidney disfunction after LT based on MELD score-based liver allocation policy implementation. Lee et al failed to demonstrate differences between three ages (1996–2000 / 2001–2005 / 2006–2008) in identifying chronic kidney disease in a cohort of 431 patients after 6 months of LT [ 21 ]. Leithead et al shows increase in incidence of AKI over 3 study periods (2000–2003, 2004–2007 and 2008–2011) even after adjusted for confounding variables [ 22 ].…”
Section: Introductionmentioning
confidence: 99%